Sport, Development, Social Change and Sport Management Degree Programs - Kluka Dean, Darlene A.; Goslin, Anneliese (ACTIVIDAD FÍSICA Y CIENCIAS / PHYSICAL ACTIVITY AND SCIENCE, 2022)
In the 21st Century, the international community faces increasingly serious and persistent social challenges. War, poverty, natural disasters, and the lack of human rights are among many conditions that are literally destroying communities throughout the world. Sport is often advocated as the glue that holds communities together by influencing daily life, social networks and community assimilation. It does, however, need to be managed in a way to foster desired social inclusion and community development (Skinner, Zakus and Cowell, 2008). Institutional frameworks and academic curricula need to recognize and institutionalize sport’s contribution to social change, and societal transformation through regional and global social agendas. For sport to contribute to a social agenda requires cooperation with other sectors in society. Sport cannot build social change and societal transformation on its own. Its strength lies in the synergy with all sectors of society. A social agenda implies a vision and an action plan to improve the well-being of people in a particular area. It provides opportunity to better coordinate, integrate, synchronize and improve policies and programs to ensure people’s well-being. The ultimate purpose of a social agenda should be to balance and connect social development with economic development within a particular area. Although social agendas will differ from region to region, one specific global social agenda highlights social challenges generally to the world. The United Nations acted as a driver for the global movement to identify social issues that affect the well-being of all people. The global social agenda is referred to as the Millennium Development Goals (MDGs) and address the following global social goals to improve well-being on a global scale.